2007
DOI: 10.3174/ajnr.a0527
|View full text |Cite
|
Sign up to set email alerts
|

Improved Visibility of the Subthalamic Nucleus on High-Resolution Stereotactic MR Imaging by Added Susceptibility (T2*) Contrast Using Multiple Gradient Echoes

Abstract: SUMMARY:Reliable identification of the subthalamic nucleus (STN) is a critical step in deep brain stimulation for Parkinson disease but difficult on T1-weighted stereotactic MR imaging. By simultaneous imaging of multiple gradient echoes, susceptibility contrast is added to conventional T1-weighted high-resolution MR image. Thus, the visibility of the STN is enhanced on a second colocalized dataset by exploiting the sensitivity of the T2*-relaxation to local iron deposits. The feasibility is underpinned by qua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
23
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(24 citation statements)
references
References 6 publications
1
23
0
Order By: Relevance
“…T2WI is the gold standard for STN imaging at 1.5 T. 11 However, T2WI may be altered by higher spatial distortions at higher magnetic fields. 3 The 3D-SPACE-FLAIR sequence at 3 T provided a good delineation of STN in clinical-compatible acquisition-time durations, because it is less sensitive to susceptibility artifacts and less sensitive to geometrical distortion artifacts than T2WI sequences at 3 T, and it constitutes convenient imaging for stereotactic procedures at 3 T. 24 Potential geometric distortions at 3 T were evaluated as minimal by comparison with NHP histology.…”
Section: Discussionmentioning
confidence: 99%
“…T2WI is the gold standard for STN imaging at 1.5 T. 11 However, T2WI may be altered by higher spatial distortions at higher magnetic fields. 3 The 3D-SPACE-FLAIR sequence at 3 T provided a good delineation of STN in clinical-compatible acquisition-time durations, because it is less sensitive to susceptibility artifacts and less sensitive to geometrical distortion artifacts than T2WI sequences at 3 T, and it constitutes convenient imaging for stereotactic procedures at 3 T. 24 Potential geometric distortions at 3 T were evaluated as minimal by comparison with NHP histology.…”
Section: Discussionmentioning
confidence: 99%
“…Because the similarity function of the registration procedure is based on structural information, accuracy of normalization will improve with optimized MR imaging sequences, with an improved contrast-to-noise ratio specific for the STN 52 or GPi. Recently, fast short time inversion-recovery images were shown to provide better differences in signal intensity between the STN and the substantia nigra and offered improved visibility of the inferior margin of the STN when compared with FSE T2-weighted MR imaging sequences, which provide better visibility of all other margins of the STN.…”
Section: Discussionmentioning
confidence: 99%
“…58 Other authors compared the location of the STN as obtained by direct localization at 3T with a computer-aided atlas-based procedure for automatic STN identification and showed that there was good agreement between the direct identification of the STN at 3T and the automatically identified structures. 65 More recently a multi-gradient-echo fast low-angle shot technique to visualize the STN, 66 exploiting the increased sensitivity of T2* to local iron deposits, has been used. This 3D MR imaging technique enables simultaneous acquisition of T1-weighted images for stereotactic use and images with superimposed T2* contrast to localize the STN.…”
Section: Practical Determination Of Target Coordinatesmentioning
confidence: 99%